A validated stability‐indicating ultra performance liquid chromatography method for the determination of potential process‐related impurities in eplerenone. Issue 15 (4th July 2016) - Du, Mingluo; Pan, Chunyan; Chen, Jing; Song, Min; Zhu, Tingting; Hang, Taijun
Abstract : A simple, sensitive, and accurate stability‐indicating analytical method has been developed and validated using ultra high performance liquid chromatography. The developed method is used to evaluate the related substances of eplerenone (EP). The degradation behavior of EP under stress conditions was determined, and the major degradants were identified by ultra high performance liquid chromatography with tandem mass spectrometry. The chromatographic conditions were optimized using an impurity‐spiked solution, and the samples, generated from forced degradation studies. The resolution of EP, its potential impurities, and its degradation products was performed on a Waters UPLC BEH C18 column (50 × 2.1 mm, 1.7 μm) by linear gradient elution using a mobile phase consisting of 10 mmol/L ammonium acetate adjusted to pH 4.5, methanol and acetonitrile. A photo‐diode array detector set at 245 nm was used for detection. The flow rate was set at 0.3 mL/min. The procedure had good specificity, linearity (0.02–3.14 μg/mL), recovery (96.1–103.9%), limit of detection (0.01–0.02 μg/mL), limit of quantitation (0.03–0.05 μg/mL), and robustness. The correction factors of the process‐related substances were calculated.